Intensity ratios of H lines: Departures from the ideal conditions in the range of laser-induced breakdown spectroscopy experiments - Cruzado, Alicia (2007)
In the present paper we analyze the behavior of H line intensity ratios with electron density and electron temperature in intermediate-density plasmas. We analyze the influence on the line intensity ratios of (1) the departures from local thermodynamic equilibrium (LTE) of the level population ratios, (2) the plasma opacity, and (3) the lowering of the ionization potential. We look, particularly, at the lines Hα, Hβ, Hγ, and Hδ and the energy levels involved in the corresponding atomic transitions for their use as diagnostics in laser-induced breakdown spectroscopy (LIBS) experiments. One important conclusion is that, for typical values of the plasma dimension and the electron temperature taking place in LIBS, i.e., L = 1 mm and Te = 10 000 K, respectively, the intensity ratios Hβ/Hα, Hγ/Hα and Hδ/Hα depart from the ideal values by less than 10% in the interval 0.65 × 1014 part/cm3 ≤ NHI ≤ 3.6 × 1017 part/cm3, which means 1 × 1014 part/cm3 ≤ Ne, ≤ 1 × 10 16 part/cm3 for a gas of pure hydrogen. For higher densities, the departures from ideal conditions increase very quickly due to opacity effects.